DEVELOPING STUDENT’S WORKSHEET IN WRITING DESCRIPTIVE TEXT BASED ON SCIENTIFIC APPROACH FOR GRADE 10 MAN BINJAI - Indana Zulfa Utami; Sumarsih Sumarsih (Universitas Negeri Medan, 2021)
The aims of this study were to develop materials of student’s worksheet in writingdescriptive text based on scientific approach for grade 10 MAN Binjai. This study wasconducted by using Research and Development (R & D) method. The data werecollecting through observing, interview and questionnaires. The results of this researchfound that the worksheet in writing descriptive text for students was not based on thescientific approach that applied scientific approach and student faced problems and haddifficulties in learning the writing skill. Researcher developed worksheet by usingScientific Approach and based on experts judgement of validating, it was appropriate tobe used by the tenth grade students of MAN Binjai to develop their skill in writingdescriptive text.